Efficient industrial dye decolorization by Bacillus sp. VUS with its enzyme system - Dawkar, Vishal V.; Jadhav, Umesh U.; Tamboli, Dhawal P.; Govindwar, Sanjay P. (Ecotoxicology and Environmental Safety, 2010)
This work presents role of different enzymes in decolorization of industrial dye Orange T4LL by Bacillus sp. VUS. Bacillus sp. strain VUS decolorized dye Orange T4LL, under static anoxic condition in 24 h. During decolorization of Orange T4LL a significant induction in the activities of lignin peroxidase, tyrosinase, and reductases (NADH-DCIP, azo, and riboflavin) was observed. The biodegradation was monitored by Ultraviolet-visible spectroscopy, Fourier transform infrared spectroscopy, and high performance liquid chromatography. The final products 4-methyl-2-o-tolylazo-benzene-1,3-diamine and [3-(phenyl-hydrazono)-cyclohexa-1,4-dienyl]-methanol were characterized by gas chromatography-mass spectroscopy. Phytotoxicity, COD, and BUD revealed non-toxicity of degraded products. Phytotoxicity study demonstrated non-toxicity of the biodegraded products for crop plants with respect to Triticum aestivum and Sorghum bicolor. Bacillus sp. VUS with its enzyme system could be a useful tool for textile effluent treatment. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Decolorization; GC-MS; Lignin peroxidase; Orange T4LL; Phytotoxicity; Reductases

Degradation of tannic acid by cold-adapted klebsiella sp NACASA1 and phytotoxicity assessment of tannic acid and its degradation products - Jadhav, Umesh; Kadu, Sudhir; Thokal, Nilesh; Padul, Manohar; Dawkar, Vishal V.; Chougale, Ashok D.; Salve, Abhay; Patil, Manoj (Environmental Science and Pollution Research, 2011)
The focus of the present study is to know the potential of bacterial isolate for tannic acid degradation at low temperature. Also, we tried to evaluate the suitability of phytotoxicity testing protocol for the determination of tannic acid toxicity. Screening for tannic acid degrading bacterial strains was carried out by using microbial isolation techniques. The 16S rDNA amplicon of the isolate was used to identify the isolate. The effect of different concentrations of tannic acid and its degradation products on germination of Vigna unguiculata was evaluated. The study was carried out to determine total sugar and starch content of the used seeds and even to check the presence of alpha-amylase activity during seed germination. The isolated bacterium was identified as Klebsiella sp NACASA1 and it showed degradation of tannic acid in 40 (+/- 0.85***) h at 15A degrees C and pH 7.0. A gradual decrease in root/shoot length was observed with increasing concentration of tannic acid. There was 95.11 (+/- 0.24**)% inhibition in alpha-amylase activity at 20,000 ppm tannic acid, as compared to control. No such effects were observed on germination, root-shoot length, and alpha-amylase activity with tannic acid degradation products. The results obtained confirmed that tannic acid may act as a toxic agent in plant cells. The simple biodegradation process presented in this study was found to be effective in reducing toxicity of tannic acid. Also, it reveals the potential of soil bacterium to degrade tannic acid at low temperature.
Keywords: Cold-adapted bacterium; Phytotoxicity; Tannic acid degradation